Effect of Low Impact Aerobic Exercise Against Lowering Depression Levels In Female Inmates at Denpasar Correctional Institution. - Ni Made Meilan Purnamasari B.W (Coping: Community of Publishing in Nursing, 2013)
Depression occurs when the stress experienced by a person does not go away, and correlated with the dramatic incidents over a person, just like a feeling of loss, feelings of helplessness, as well as situations that lower self-esteem, this condition is similar to that that is experienced by female inmates in correctional institutions. The loss of freedom and lack of physical activity have also significant influence to the condition of inmates ‘depression. This results in not optimal blood circulation. Oxygen and nutrients carried throughout the body and brain also decline, causing the decline in brain metabolism and the production of neurotransmitters, including serotonin and norepinephrine in the limbic system that play the role in making depression. One effort to overcome is doing regular and structural physical activity by doing low impact aerobics. This study aims to find out there is effect of low impact aerobics to decrease levels of depression in female inmates. This study uses the design of one group pre-test and post-test design. The sample of 50 people selected using purposive sampling. Data is collected by using questionnaires Beck Depression Inventory (BDI) II. The results of study showed there is difference in the average level of depression before and after given the low impact aerobics for t = 10.176. Test results of paired sample t-test (p <0.05) obtained p-value = 0.000 <0.05, it can be stated there is significant impact of low impact aerobics on reducing levels of depression to female inmates at Denpasar Correctional Institution. Based on this study, it is suggested that female inmates routinely do low impact aerobics so it can help lower levels depression.